ESA Knowledge Management Agenda - Mugellesi Dow, Roberta; Guerrucci, Damiano; Argamasilla, Raul Cano; Bernardino, Diogo; Pallaschke, Siegmar (Knowledge Discovery, Knowledge Engineering and Knowledge Management, 2015)
During the last years, ESA has gathered an extensive experience in Knowledge Management (KM). As a knowledge-intensive organisation, ESA needs to implement an efficient management of its expertise and know-how. To this purpose, an ESA corporate KM initiative was conducted during the last few years and consisting of several pilot projects. The selected approach was built on pillars summarized in these four keywords: “integrated” (interconnection of its parts), “pragmatic” (concrete solutions compatible with the corporate culture), “business” (linked to the core business) and “open” (input and best practices gathered inside and outside the Agency). This paper presents the activities carried out within this set of pilots and the relations among them. The pilot projects presented in the paper are: the KM Portal called iKnow, the Competency Management Tool, the Expertise Directory, the Knowledge Capture and Handover process, the KM Officer and Lessons Learned Harmonization. The future of KM in ESA is a challenge aiming at proposing integrated solutions in an environment with different cultures and several existing individual solutions. The achievement of it will certainly provide a better leverage for the institutional KM.